M-powering marketing in a mobile world - Banerjee, Syagnik (Digital and social media marketing and advertising collection., 2018)
The mobile, device-led integration of online and offline worlds has introduced many uncertainties and opportunities. These have driven businesses, researchers, and policymakers to learn more about this rapidly changing domain. To help businesses compete, survive, and thrive in this transforming environment, it is essential to structure their understanding of the field and provide conceptual frameworks as decision aids. In M-Powering Marketing in a Mobile World, we present a concise guide for executives in general, digital marketers, and for interested researchers and policymakers. We identify key emerging trends, develop frameworks based on critical variables, and draw lessons for marketers. The book illustrates the processes by which mobile devices have transformed economies worldwide, the evolving face of Internet usage, strategies adopted by corporations, their applications in retail, emerging data and metric generation processes, as well as policy issues. It explains how mobile devices have become the market's steppingstone toward an IoT-infused environment, a gateway for artificial intelligence-driven marketing processes and the entry portal for a potentially hyperautomated future of consumption.